In space we read time : on the history of civilization and geopolitics - Schlögel, Karl (2016)
Umfang und Inhalt: "History is usually thought of as a tale of time, a string of events flowing in a particular chronological order. But as Karl Schlogel shows in this groundbreaking book, the where of history is just as important as the when. Schlogel relishes space the way a writer relishes a good story: on a quest for a type of history that takes full account of place, he explores everything from landscapes to cities, maps to railway timetables. Do you know the origin of the name 'Everest'? What can the layout of towns tell us about the American Dream? In Space We Read Time reveals this and much, much more. Here is both a model for thinking about history within physical space and a stimulating history of thought about space, as Schlogel reads historical periods and events within the context of their geographical location. Discussions range from the history of geography in France to what a town directory from 1930s Berlin can say about professional trades that have since disappeared. He takes a special interest in maps, which can serve many purposes–one poignant example being the German Jewish community's 1938 atlas of emigration, which showed the few remaining possibilities for escape. Other topics include Thomas Jefferson's map of the United States; the British survey of India; and the multiple cartographers with Woodrow Wilson at the Paris Peace Conference, where the aim was to redraw Europe's boundaries on the basis of ethnicity. Moving deftly from the Austro-Hungarian Empire to 9/11 and from Vermeer's paintings to the fall of the Berlin wall, this intriguing book presents history from a completely new perspective"–(Provided by publisher.)